각막굴절교정술 렌즈 치료영역의 이측편위가 파장가변 빛간섭단층촬영계상 각막 수차에 미치는 영향 - 허정선(Jung Sun Heo); 문남주(Nam Ju Moon); 김경우(Kyoung Woo Kim) (Daihan angwa haghoi jabji, 2024)
목적: 각막굴절교정술 렌즈 치료영역의 이측편위가 전안부 파장가변 빛간섭단층촬영계로 측정한 각막 수차에 미치는 영향을 알아보았다. 대상과 방법: 각막굴절교정술 렌즈 착용 후 전안부 파장가변 빛간섭단층촬영계(Anterion, Heidelberg Engineering, Heidelberg, Germany)상 전면, 후면 및 전체 각막난시, 전면 및 전체 각막의 1-4차 개별 수차의 절대값, 4-7차 root mean square (RMS), 저위및 고위수차 RMS를 수집하였다. 중심이탈이 없는 대조군(no decentration, ND)과 이측편위 환자군(temporal decentration, TD)으로구분하여 수집값들을 군 간 비교하였다. 결과: 총 32명 61안(ND군 44안, TD군 17안)이 분석에 포함되었다. TD군의 이측편위 평균 거리는 0.74 ± 0.15 mm였다. 기저 안축장, 구면대응치, 전면 평균 각막굴절력 및 전면 각막난시는 군 간 차이가 없었다. TD군에서 ND군 대비 전면 및 전체 각막의 horizontal tilt와 수평 코마가 더 높았고, with-the-rule (WTR)/against-the-rule (ATR) astigmatism이 더 낮았다. 전면 및 전체 각막 5차 RMS, 저위수차 RMS 및 고위수차 RMS 모두 TD군에서 ND군 대비 더 높았다. 두 군 간 근시교정량에는 유의한 차이를 보이지 않았다. 결론: 각막굴절교정술 렌즈 치료영역의 이측편위 발생 시, 비록 근시 감소 효과는 유의한 영향을 받지 않았지만 전면 및 전체 각막의저위 및 고위수차 RMS가 증가하고 개별 수차 중에서는 저위수차인 horizontal tilt와 고위수차인 수평 코마가 증가하였다. Purpose: This study used anterior segment swept-source optical coherence tomography (AS SS-OCT) to explore the effect of temporal decentration within the orthokeratologic lens treatment zone on corneal aberrations. Methods: After lens placement, AS SS-OCT was used to evaluate anterior, posterior, and total corneal astigmatism and the magnitudes of the individual 1st- to 4th-order aberrations of the anterior and entire corneal fields. Also, the 4th-to 7th-order root mean square (RMS), and the low- and high-ordered RMSs of both the anterior and entire corneal areas were recorded. We compared subjects lacking (the no decentration [ND] group) to those exhibiting (the temporal decentration [TD] group) temporal decentration. Results: In all, 61 eyes of 32 patients (44 eyes in the ND group and 17 in the TD group) were included. In the TD group, the average temporal decentration was 0.74 ± 0.15 mm. The baseline axial length, spherical equivalent, anterior mean corneal power, and anterior corneal astigmatism did no difference between the two groups. However, the TD group exhibited more anterior and total corneal horizontal tilts, and horizontal coma, than the ND group. That group also had less with-the-rule (WTR)/against-therule (ATR) astigmatism, elevated anterior and total corneal 5th-order RMS values, and greater low- and high-ordered RMS levels. However, despite these differences, the extent of myopia correction did not significantly differ between the groups. Conclusions: Although myopia reduction was not significantly compromised by temporal decentration of an orthokeratologic lens, the anterior and total corneal low- and high-ordered RMS values increased. In terms of individual aberrations, the low-ordered horizontal tilt and the high-ordered horizontal coma increased. KCI Citation Count: 0